If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 = 3 + w Solving 6 = 3 + w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-1w' to each side of the equation. 6 + -1w = 3 + w + -1w Combine like terms: w + -1w = 0 6 + -1w = 3 + 0 6 + -1w = 3 Add '-6' to each side of the equation. 6 + -6 + -1w = 3 + -6 Combine like terms: 6 + -6 = 0 0 + -1w = 3 + -6 -1w = 3 + -6 Combine like terms: 3 + -6 = -3 -1w = -3 Divide each side by '-1'. w = 3 Simplifying w = 3
| -b=-2b-4 | | 8x-200=-9+7x | | 10x+14+6+6x=180 | | 8y-9-3y+8=0 | | 6x+7-3x=4-5x | | 3p+444=-999+2p | | 140+150m=260+120m | | x(4-x^2)=8-x^3 | | (a^2-24-2a)x=a^2-10a+16 | | x+141=2x-369 | | 2g=6-g | | 29=X+X+7 | | 14.75=2x+x-6.25 | | 28=b+5 | | 10a+13=20a-387 | | 25x-4=3x+4 | | -5+7h=10+4h | | s=c+cv | | 14x=-2(777-6x) | | 10c=-8c+8 | | 8m-9=5m | | 5f=125 | | 0=4x^2+9x-9 | | -8u+6=-9u | | 2(x+4)=5(2x-8) | | -2p-5=-15 | | 8x+5=6x+20 | | -2p-5=15 | | -2=x-3y | | -14x^2=49 | | p+7774=5p+3p-80 | | 180=90+3x+1+2x+4 |